Ketahanan Pangan di Kawasan Timur Indonesia - Rachmaningsih, Triana; Priyarsono, D. S. (Jurnal Ekonomi dan Pembangunan Indonesia, 2012)
This study aims at analyzing the dynamics of food security and the factors that influence food security in Eastern Indonesia. The methodology used is panel data tobit model of 190 districts/municipalities in the Eastern Indonesia from 2008 to 2010. Based on the classification of the food security degree, the majority of households in Eastern Indonesia are categorized as the vulnerable. Food security is affected by percentage of poor people, GRDP per capita, female illiteracy rate and average years of schooling. Based on the elasticity, education has the highest contribution in improving food security in the Eastern Indonesia.